Menilai Pengalaman Pengguna terhadap Aplikasi Tata Kelola Pelanggan RT-RW NET Menggunakan User Experience Questionnaire (UEQ) - Rofiuddin Rofiuddin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
User experience is one of the key factors in determining the success of an application, because it plays an important role in providing impressions and comfort to users. This research aims to evaluate the user experience of the RT-RW NET Customer Governance application using the User Experience Questionnaire (UEQ) method, a method designed to measure important aspects of user experience. A total of 33 respondents who were active users of this application were involved in the research. The results of the analysis show that the aspects of attractiveness, clarity, efficiency and stimulation received positive assessments, with the highest scores for attractiveness (1.84) and clarity (1.82). However, the novelty aspect received a lower score (1.79), indicating a need for further development and innovation. The conclusion of this research is that the RT-RW NET Customer Governance application provides a good and satisfying user experience, but improvements need to be made in the novelty aspect so that this application can reach a more optimal and competitive level of user experience. This research contributes to developers in understanding the strengths and weaknesses of applications to support the development of better applications in the future.